2022
DOI: 10.1055/s-0042-1755259
|View full text |Cite
|
Sign up to set email alerts
|

From Esthetic Medicine to Optimizing Reconstructive Outcome: A Feasibility Trial on Secondary Refinement of Fasciocutaneous Anterolateral Thigh Flaps with Cryolipolysis

Abstract: Background Free adipocutaneous anterolateral thigh (ALT) flaps have evolved as workhorse flaps to reconstruct complex, multicompound defects. While coverage is safely achieved, flaps may remain bulky. As a standard of care, flaps are refined with liposuction, partial excision, or combination of both. Cryolipolysis is widely used for fat reduction in esthetic medicine. This pilot comparative study analyses whether cryolipolysis may serve as a safe alternative method to effectively reduce volume in fasciocutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A novel and less invasive strategy in thinning a flap can be the use of cryolipolysis as described recently by Nagel et al 36 Cryolipolysis showed to be effective in reducing both the subcutaneous adipose tissue layer and the flap circumference.…”
Section: Discussionmentioning
confidence: 99%
“…A novel and less invasive strategy in thinning a flap can be the use of cryolipolysis as described recently by Nagel et al 36 Cryolipolysis showed to be effective in reducing both the subcutaneous adipose tissue layer and the flap circumference.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to direct excision, liposuction, tissue shaving with an arthroscopic cartilage shaver, cryolipolysis, and skin grafting are methods of debulking flaps ( 6 , 7 ). Direct excision is the first method of consideration for flap debulking.…”
Section: Discussionmentioning
confidence: 99%
“…10,12 Recently, cryolipolysis has been used outside of the context of fat reduction for cosmetic purposes, including secondary refinement of fasciocutaneous anterolateral thigh flaps, regression of lipedematous scalp, and treatment of notalgia paresthetica. [13][14][15] As the use of noninvasive procedures to reduce body fat continues to grow, both in and out of the cosmetic world, it is important to continuously review and appropriately document adverse events and complications in clinical practice. Healthcare professionals must stay abreast of these new insights so that they can inform their patients about these potential risks.…”
Section: Introductionmentioning
confidence: 99%